Effects of ketoprofen on rice seedlings: Insights from photosynthesis, antioxidative stress, gene expression patterns, and integrated biomarker response analysis. (August 2020) - Wang, Huan; Jin, Mingkang; Xu, Linglin; Xi, Hao; Wang, Binhui; Du, Shaoting; Liu, Huijun; Wen, Yuezhong
Abstract: Pharmacologically active compounds found in reclaimed wastewater irrigation or animal manure fertilizers pose potential risks for agriculture. The mechanism underlying the effects of ketoprofen on rice ( Oryza sativa L.) seedlings was investigated. The results showed that low concentrations (0.5 mg L −1 ) of ketoprofen slightly stimulate growth of rice seedlings, while high concentrations can significantly inhibit growth by reducing biomass and causing damage to roots. Ketoprofen affects photosynthetic pigment content (Chla, Chlb, and carotenoids) and chlorophyll synthesis gene ( HEMA, HEMG, CHLD, CHLG, CHLM, and CAO ) expression. Fluorescence parameters such as minimum fluorescence (F0 ), maximum fluorescence (Fm ), variable fluorescence (Fv ), potential photosynthetic capacity (Fv /F0 ), maximum quantum efficiency of PSII photochemistry (Fv /Fm ), electron transfer rate (ETR), and Y(II), Y(NPQ), Y(NO) values were affected, showing photosynthetic electron transfer was blocked. Active oxygen radical (O2 −and H2 O2 ), malondialdehyde and proline content increased. Superoxide dismutase, catalase and ascorbate peroxidase activities, glutathione content and antioxidant-related gene ( FSD1, MSD1, CSD1, CSD2, CAT1, CAT2, CAT3, APX1, APX2 ) expression were induced. Higher integrated biomarker response values of eight oxidative stress response indexes were obtained at higher ketoprofen concentrations. Ultrastructure observation showed that ketoprofen causes cell structure damage, chloroplast swelling, increase in starch granules, and reduction in organelles. This study provides some suggested toxicological mechanisms and biological response indicators in rice due to stress from pharmacologically active compounds. Graphical abstract: Image 1 Highlights: Ketoprofen affects chlorophyll content, gene expression and electron transfer. Antioxidant enzymes activity and antioxidant-related gene expression increased. Has higher IBR value of oxidative stress response indexes at higher concentration. Cell structure of shoot and root was damaged by ketoprofen. Abstract : The mechanism of photosynthesis and oxidative stress response of rice caused by ketoprofen were revealed.